HUBUNGAN DURASI PENGGUNAAN GADGET DENGAN KELUHAN SUBJEKTIF GANGGUAN KESEHATAN MATA PADA MAHASISWA FAKULTAS KEPERAWATAN UNIVERSITAS RIAU - Sangkot Hani Rizki; Darwin Karim; Erwin Erwin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2021)
Gadgets can emit several rays, including ultraviolet rays, X-rays, low-frequency electromagnetic radiation that can cause eye damage. Using gadgets for too long can affect eye health. One of the health impacts that can be caused by the duration of using gadgets is more than the maximum limit, one of which is eye complaints. This study aims to determine the relationship between the duration of gadget use and subjective complaints of eye health problems in students of the Faculty of Nursing, Riau University. Methods: This research is quantitative with a coss sectional design. The research location is at the Faculty of Nursing, Riau University. The sample technique of this research is purposive sampling, with a total sample of 30 people who meet the inclusion criteria. Data analysis used univariate analysis and bivariate chi-square test. Results: Bivariate analysis The results of statistical tests using the chi square test, obtained p value 0.072 > 0.05, which means Ho failed to be rejected. Conclusion: There is no relationship between the duration of gadget use and subjective complaints of eye health problems in students of the Faculty of Nursing, Riau University. Keywords: fatigue eye, gadget, gadgets use